EFEKTIVITAS PENERAPAN METODE TOTAL PHYSICAL RESPONSE WITH PICTURES TERHADAP PENGUASAAN KOSAKATA BAHASA INGGRIS SISWA ( Penelitian Quasi Experiment di Kelas III SDN 1 Setiawaras dan SDN Sindangheula Kecamatan Cibalong Kabupaten Tasikmalaya) - LESTARI, Wini Citra (2014)
This Research is motivated by the low of mastery of the English vocabulary in the lower class. To overcome these problems, the researchers applied the Total Physical Response method with Pictures because it can help students to remember the phrase or words in a fun learning conditions so as to reduce the anxiety of students in learning (affective filter). The purpose of this research it was to find out the students' mastery of english vocabulary that use Total Physical Response method with Pictures when compared to the conventional method. The method which used in this research is the study of quasi experiment research with the kind is nonequivalent control group. The population in this research is a third-grade students at SDN 1 Setiawaras and SDN Sindangheula Cibalong sub-district of Tasikmalaya district, with a non-probability sampling technique with the kind of saturated samples which consist of experiment class and control class. Data collection techniques which used is writing test techniques about the students' english vocabulary with the theme of musical instruments. Analysis of the data which used in this research is analysis quantitative with help by Microsoft Excel 2007 and SPSS 16.0. Based on the analysis of data, it can be concluded that the increase in students' english vocabulary in the classroom experiments which using Total Physical Response method with Pictures is better than the english vocabulary of elementary school students in the control class which using conventional methods. The teachers should be able to apply the variation methods in teaching vocabulary to students which is the basis for a variety of language skills. Total Physical Response with Pictures effective to be applied in learning English vocabulary in a low grade. Keywords : Total Physical Response with Pictures Method, Vocabulary Mastery. Penelitian ini dilatarbelakangi oleh rendahnya penguasaan kosakata bahasa Inggris di kelas rendah. Untuk mengatasi permasalahan tersebut, maka peneliti menerapkan metode Total Physical Response with Pictures karena dapat membantu siswa untuk mengingat frase atau kata-kata dalam pembelajaran dengan kondisi yang menyenangkan sehingga dapat mengurangi kecemasan siswa dalam belajar (affective filter). Tujuan dari penelitian ini adalah untuk mengetahui peningkatan penguasaan kosakata bahasa Inggris siswa yang menggunakan metode Total Physical Response with Pictures bila dibandingkan dengan yang menggunakan metode konvensional. Metode penelitian yang digunakan oleh peneliti adalah penelitian quasi experiment dengan jenis nonequivalent control group. Populasi dalam penelitian ini adalah siswa kelas III SDN 1 Setiawaras dan SDN Sindangheula Kecamatan Cibalong Kabupaten Tasikmalaya, dengan teknik pengambilan sampel nonprobability sampling dengan jenis sampel jenuh yang terdiri dari kelas eksperimen dan kelas kontrol. Teknik pengumpulan data yang digunakan adalah teknik tes dengan jenis tes tulis tentang penguasaan kosakata bahasa Inggris siswa dengan tema musical instruments. Analisis data yang digunakan adalah analisis data kuantitatif dengan menggunakan bantuan program Microsoft Excel 2007 dan program SPSS 16.0. Berdasarkan hasil analisis data, maka dapat disimpulkan bahwa peningkatan kemampuan penguasaan kosakata bahasa Inggris siswa di kelas eksperimen yang menggunakan metode Total Physical Response with Pictures lebih baik bila dibandingkan dengan peningkatan kemampuan penguasaan kosakata bahasa Inggris siswa SD di kelas kontrol yang menggunakan metode konvensional. Guru harus mampu menerapkan metode-metode bervariasi terutama dalam mengajarkan kosakata kepada siswa yang merupakan dasar dalam berbagai keterampilan berbahasa. Total Physical Response with Pictures efektif untuk diterapkan dalam pembelajaran kosakata bahasa Inggris di SD kelas rendah. Kata Kunci : Metode Total Physical Response with Pictures, Penguasaan Kosakata.